The Effects of Daily Melatonin Gavage on Reproductive Activity in the Male Syrian Hamsters - Jeon, Geon Hyung; Kim, Hyeon Jeong; Park, Jinsoo; Lee, Sung-Ho; Cheon, Yong-Pil; Choi, Donchan (Balsaeng'gwa saengsig, 2020)
The proper administration of melatonin has well been documented to induce testicular regression in seasonal breeding animals. The subcutaneous injections of melatonin in the afternoon, not in the morning, consistently occurred testicular involution in the male Syrian (golden) hamsters whose reproductive activity is regulated by the photoperiod. But the effects of daily melatonin via gavage have not been estimated. Golden hamsters housed in long photoperiod (LP) were divided into 5 groups: the control animals housed in LP or in short photoperiod (SP) and animals treated daily with low (15 μg), middle (150 μg), and high dosages (1,500 μg) of pure melatonin by using gavage in the evening for 8 weeks. As results, LP control animals had large testes and SP controls displayed small and entirely regressed testes. The animals treated with various dosages of melatonin showed collectively degenerating effects on the weights of testes, epididymides, and seminal vesicles in the middle and high dosage groups, with the individual differences as well. The high dosages induced testicular regression in more proportion than the middle dosages did. The low dosage had large testes like the LP control animals. The small and inactive testes shown in some animals of both middle and high groups presented the complete regression as those of the animals maintained in SP. These results strongly suggest that the administrations of melatonin lead to testicular involution in the male golden hamsters when it is administered through gavage.